nargiza ROLE OF MODERN TECHNOLOGIES AND STRATEGIES IN LEARNING ENGLISH: ROLE OF MODERN TECHNOLOGIES AND STRATEGIES IN LEARNING ENGLISH - Mardanova, Nargiza (Журнал иностранных языков и лингвистики, 2022)
In our period all sides of life are developing with modern technologies very quickly. This condition belongs to modern technology. All of us need these innovative technologies every day. These technologies can be good helpers with us. When we use them we have a lot of opportunities and conveniences. We can finish our work without any problem by using them. Well, How they role in learning English? Which advantages they have? Do we know about them?